Analytical models for β‐diversity and the power‐law scaling of β‐deviation. Issue 3 (2nd December 2020) - Xing, Dingliang; He, Fangliang
Abstract: β ‐diversity is a primary biodiversity pattern for inferring community assembly. A randomized null model that generates a standardized β ‐deviation has been widely used for this purpose. However, the null model has been much debated and its application is limited to abundance data. Here we derive analytical models for β ‐diversity to address the debate, clarify the interpretation and extend the application to occurrence data. The analytical analyses show unambiguously that the standardized β ‐deviation is a quantification of the effect size of non‐random spatial distribution of species on β ‐diversity for a given species abundance distribution. It robustly scales with sampling effort following a power law with exponent of 0.5. This scaling relationship offers a simple method for comparing β ‐diversity of communities of different sizes. Assuming log‐series distribution for the metacommunity species abundance distribution, our model allows for calculation of the standardized β ‐deviation using occurrence data plus a datum on the total abundance. Our theoretical model justifies and generalizes the use of the β null model for inferring community assembly rules.